Рассказы о Гагарине - Нагибин Юрий Маркович (Дет. лит., 2011)
Экземпляры: С/а ДБ, ф. 1, 2, 3, 4 (20111031) / Инвентарный номер: 97563 / Цена: 173.52 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 16 / ББК: 84(2Рос=Рус)6